2018
DOI: 10.5897/ajbr2018.0992
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of vitamin C on caspase 9 and oxidative stress in rheumatoid arthritis patients

Abstract: Rheumatoid arthritis (RA) is a chronic and an autoimmune disease of the joints and is widely distributed worldwide. It is characterized by alterations of the antioxidant defense system and increased free radical formation and pro-inflammatory cytokine. The aim of the present study was to evaluate the effect of vitamin C supplementation on oxidative stress biomarkers and caspase 9 level in rheumatoid arthritis patients. This study included 30 RA patients and 30 healthy subjects. Plasma levels of malondialdehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…A previous study indicated that apelin delayed the onset of apoptosis for a few hours in human enterocyte model (Caco-2), followed by enhanced apoptosis. The antiapoptotic effect of apelin was demonstrated to be as a result of enhanced anti-apoptotic Bcl-2 family proteins synthesis and interaction with phosphatidylinositol 3-kinase protein, whereas its proapoptotic activity may be attributable to suppressed expression of 8-oxoguanine DNA glycosylase1/2 (OGG1/2), DNA oxidative damage repair enzyme, leading to impaired oxidative DNA repair and induction of apoptosis through the mitochondrial apoptotic pathway [74,75]. A previous study reported elevated plasma levels of 8-hydroxy-2 -deoxyguanosine, the cleavage product of OGG enzyme, in RA patients indicating its higher activity to overcome the localized oxidative stress in the RA synovium [76].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that apelin delayed the onset of apoptosis for a few hours in human enterocyte model (Caco-2), followed by enhanced apoptosis. The antiapoptotic effect of apelin was demonstrated to be as a result of enhanced anti-apoptotic Bcl-2 family proteins synthesis and interaction with phosphatidylinositol 3-kinase protein, whereas its proapoptotic activity may be attributable to suppressed expression of 8-oxoguanine DNA glycosylase1/2 (OGG1/2), DNA oxidative damage repair enzyme, leading to impaired oxidative DNA repair and induction of apoptosis through the mitochondrial apoptotic pathway [74,75]. A previous study reported elevated plasma levels of 8-hydroxy-2 -deoxyguanosine, the cleavage product of OGG enzyme, in RA patients indicating its higher activity to overcome the localized oxidative stress in the RA synovium [76].…”
Section: Discussionmentioning
confidence: 99%